Znaczenie otoczenia (czynników wewnętrznych i zewnętrznych) w rozwoju grupy producentów truskawek z rejonu małopolski - przed wstąpieniem i po wstąpieniu Polski do Unii Europejskiej - Domagalska-Grędys, Marta (Importance of Environment (Internal and External Factors) in the Development of Strawberries Producer Groups from the Małopolska Region - Before and after the Polish Accesion to the EU, 2005)
The effectiveness of producer groups is determined by constantly changing conditions of their environment. There were made The interviews with strawberry producers of the community of Olesno provide new opinions about internal and external factors which determine the development of the group in the 2003-2004. Their opinions were changed in comparison with the time from before the accession to the EU. There is no view which relates directly to the EU's aspects in spite of clear change in producers thinking.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 155-159